The Influence of Women's Leadership Style and Work Motivation on the Performance of Police Personnel in the Legal Work Unit of the West Sumatra Regional Police Force - Mutiara Fadhiilah; Hasbullah Malau (Penerbit Jurnal Indonesia, 2024)
This study aims to analyze the Effect of Style Leadership and Work Motivation on the Performance of Police Personnel in the Legal Division work unit of the West Sumatra Regional Police. The method used in this research is a quantitative method with a descriptive approach, the research sample is 26 personnel of the Legal Division of the West Sumatra Regional Police. Data analysis was carried out using instrument tests through SPSS Version 29 for windows software to check the validity and reliability of the data. The results of data analysis show that the variable female leadership style does not have a significant effect on personnel performance, this is evidenced by the results of the hypothesis test obtained a significance value of 0.468 > 0.05 and tcount 0.739 ≤ ttabel 2.064. The results of this study also show that work motivation variables have a significant effect on personnel performance with a significance value of 0.001 < 0.05 and tcount 4.223 ≥ ttabel 2.064. Through the simultaneous hypothesis test (f test), it shows that the female leadership style and work motivation have an effect on personnel performance with a significance value of Sig 0.001 < 0.05 and the value of fcount 10.159 > ftabel 3.420.